Development of creative abilities of junior pupils by means of gaming technologies (Actual Problems of Psychology in Educational Institutions, 2018)
In the article the influence of game technologies on the development of creative abilities of primary school students has been analyzed. The level of development of creative abilities of students is researched. The types of exercises for the development of creative abilities through gaming technologies are described. Originality, non-standard images, fantasy skills, detailed description of images, emotional images are taken into account. The conclusion about the important role of gaming technologies for the development of the creative abilities of a contemporary student is drawn.
Keywords: game technologies; creative abilities; creativity; personality; primary school students